Pembuatan Prototip Dye Sensitized Solar Cell (DSSC) Berbasis Zat Warna Buah Senduduk (Melastoma Malabathricum L.) : Pengaruh Suhu Sintering TiO2 Dan Konsentrasi Elektrolit - Wilda Zakiah; Amun Amri; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Increasing demand of energy consumption enforces the development of alternative energy source to solve the world energy crisis. Dye Sensitized Solar Cell (DSCC) is a promising alternative for solar cell application of future generation which is based in semiconductors that utilizes photoelectrochemical phenomenon as basic principle to generate electricity. This research tries to make DSSC prototype with dye from melastome fruit (Melastoma Melabathricum L.). The examined variables are TiO2 sintering temperature at 300oC, 350oC, 400oC, and electrolyte concentration 0.025M, 0.05M and 0.075M of iodine. On the first step, the dye was made by diluting 20 gr of melastome fruit in aquadest, methanol, and acetic acid. Next, the coating of TiO2 by solving TiO2 powder in ethanol and deposited on spin coater and sintered by using furnace. Then the making of carbon electrode, making of electrolyte, and finally characterization of DSSC. UV-Vis spectroscopy examination result showed that melastome fruit contains anthocyanin that was proved from absorbance on wavelength of 515 nm. DSSC voltage examination showed that the higher TiO2 sintering temperature and electrolyte concentration, then the voltage generated was higher as well. The highest voltage was showed on sample with iodine electrolyte concentration of 0,075 M which is 2,385 Volt/cm2. Morphollogy test showed that TiO2 coating has porous structure with equal particle dispersion on every increment of TiO2 sintering temperature. XRD examination showed that the coating is in anatase phase and adhesion test showed that DSSC with highest voltage has adhesivity of 3B (Good).Key Word : dye sensitized solar cell (dssc), dye, electrolyte, tio2